Pengembangan Lembar Kerja Peserta Didik Eksploratif Berbasis Contextual untuk Siswa Kelas IV Sekolah Dasar - Afandi, Muhamad Sofyan; Zain, Moh. Irawan; Khair, Baiq Niswatul; Tahir, Muhamad; Hakim, Mansur; Handika, Ilham (Pendagogia: Jurnal Pendidikan Dasar, 2023)
This study aims to develop CTL-based exploratory worksheets in improving student learning outcomes. The development method used is the ADDIE model by adding contextual concepts to alternative energy materials. The application of LKPD in learning uses one group sample design. The sample used was fourth grade students at SDN 38 Cakranegara. The LKPD validation data collection technique uses a questionnaire filled out by an expert validator. The sample class underwent pre-test and post-test to see the effectiveness of LKPD in learning. The data from expert and teacher validation are categorized as valid in terms of content feasibility 74.3%, presentation 75.6%, and language 80%. The effectiveness of the LKPD is classified as effective in improving student learning outcomes as seen in the n-gain test results of 0.31 with an increase in the medium category and the t-test with a value of 0.003 below 0.05 which shows there is a significant difference between the pretest and posttest scores. Thus, the exploratory development of CTL-based worksheets is classified as valid and effective in improving student learning outcomes.